The effects of imports and economic growth in Chinese economy: A Granger causality approach under VAR framework - Khalid Usman; Usman Bashir (Journal of Risk and Financial Management, 2022)
This study inspects the association between economic growth and imports from China, based on data sourced from 2000 to 2021. For this reason, a quantitative research approach is used to determine the causality between the variables and their impact on the economy. The null hypothesis of the paper implies that the import growth rate has a significant impact on the GDP growth rate in the Peoples Republic of China. This hypothesis was rejected via the Granger causality test, as the only single directional relationship was found. However, further analysis was conducted by applying a Vector Auto-Regression (VAR) model that included leading macroeconomic variables, such as the inflation rate, the bank rate, and the exchange rate between the US dollar and Chinese yuan. The impulse responses of the model, aligned with the economic theory and the results, suggested that the import growth rate is negatively related to the GDP growth rate, while the GDP growth rate has an initial positive impact on the imports for the first three quarters, which later changes to a negative impact. This time lag suggests that while the impact between the variables is important, negative outcomes could be avoided if proper economic policy is implemented. The government of China should focus on policy implications that further promote export and substitute imported goods with domestic production.
Keywords: 650; imports; economic growth; unit root; VAR model; Granger causality test; China